Lipid metabolism in human platelets: II. De novo phospholipid synthesis and the effect of thrombin on the pattern of synthesis - Lewis, Nancy (1969)
Washed human platelets were incubated with radioactive glycerol; the platelets were able to synthesize de novo the major phosphoglycerides including phosphatidic acid, phosphatidylinositol, phosphatidyl choline, phosphatidyl ethanolamine, and phosphatidyl serine. The specific activities of the phosphoglycerides obtained after glycerol incorporation indicate that phosphatidic acid, phosphatidylinositol, and phosphatidyl choline are metabolically active relative to phosphatidyl ethanolamine and that formation of phosphatidyl serine occurs to a much more limited extent. When platelets were incubated with bovine thrombin, 1 U/ml, the pattern of glycerol incorporation into phospholipid was changed. There was a 3-fold decrease in the total incorporation into lipid in 30 min with a relative 5-fold decreased incorporation into phosphatidyl choline and phosphatidyl ethanolamine and a 5-fold increased incorporation into phosphatidyl serine. The increased incorporation into phosphatidyl serine. The increased incorporation into phosphatidyl serine was maximal within the first 2 min but was transient, since within 20 minutes, the rate returned to that seen in platelets incubated with glycerol alone. Purified human thrombin also produced this same effect on phospholipid synthesis in platelets. Trypsin produced effects on phosphoglyceride formation similar to those seen with thrombin, and the trypsin-induced effect was inhibited by prior incubation of trypsin with soybean trypsin inhibitor, suggesting that proteolysis may be required for the observed effects on phospholipid synthesis.